Кримінально-правове регулювання покарання у вигляді штрафу потребує вдосконалення - Марисюк, К. Б. (Видавництво Львівської політехніки, 2015)
Вивчаються питання кримінально-правового регулювання покарання у вигляді штрафу. Проаналізовано останні зміни у цій сфері. Висловлено авторські позиції щодо останніх. Запропоновано можливі варіанти реформування нормативно-правових положень. Автор усвідомлює, що висловлені пропозиції навряд чи зможуть повною мірою виправити усі проблеми, які існують у сфері кримінально-правового регулювання покарання у вигляді штрафу, проте однозначно слугуватимуть тією відправною точкою, яка може підштовхнути законодавця до подальших реформ у досліджуваній сфері. Статья посвящена изучению вопросов уголовно-правового регулирования наказания в виде штрафа. Проанализированы последние изменения в этой сфере. Высказаны авторские позиции относительно последних. Предложены возможные варианты реформирования нормативно-правовых положений. Автор осознает, что изложенные предложения вряд ли смогут в полной мере решить все проблемы, которые существуют в сфере уголовно-правового регулирования наказания в виде штрафа, но однозначно станут той отправной точкой, которая может подтолкнуть законодателя к дальнейшим реформам в исследуемой сфере. In the settlement of legal status of punishment in the type of fine it is possible the extraordinarily meaningful stage to count an acceptance and introduction in an action of Bill of Ukraine “About making alteration to some legislative acts of Ukraine in relation to humanizing of responsibility for offence in the field of economic activity”. Among the most meaningful changes in legal status of punishment in the type of fine, brought in by the mentioned law, following: а) the maximal size of punishment in the type of fine is megascopic from 1000 untaxable sizes of profits of citizens to 50000 untaxable sizes of profits of citizens, if it is not envisaged the articles of Special part of CC higher size of fine. Consequently, the maximal fixed size of fine is megascopic from 17000 to 850000 hryvnyas, id estin 50 times. Given out, that so considerable maximal sizes of fine can entail certain difficulties with their actual implementation. Given out, that so considerable maximal sizes of fine can entail certain difficulties with their actual implementation. Taking into account the difficult enough material situation of considerable part of population, it is possible to assume large authenticity of that through mass non-payment courts will begin convict of the fines imposed on themto replace a fine imprisonment, that will result not in humanizing of responsibility, but to it actual strengthening. b) new release of p. 2 c. 53 CC of Ukraine envisages, that the sum of fine in some cases can be appointed in size of the not less inflicted harm. A rule in obedience to that is on this occasion set: “For the commission of crime for that basic punishment is envisaged in the type of fine over three thousand untaxed minimums of profits of citizens, a size of fine that is appointed by a court can not be less than size of the property harm inflicted by a crime, or crime of profit got as a result of feasance, regardless of the maximumsize of fine, envisaged by approval of the article (by approval of part of the article) of special part of CC”. In connection with the above-mentioned arguments, suggest to bring down the maximal size of punishment is legislatively envisaged in the type of fine to the economically reasonable limit, namely at least in 3-5 times. Maintenance of present maximum seems expedient only in case of input of criminal responsibility of legal entities and only in relation to the last. Offered, that sizes of fines both in General part and in approvals of the articles of Special part of CC of Ukraine, to outline not in untaxable minimums of profits of citizens, but in monetary items (hryvnyas).
Уголовно-правовое регулирование наказания в видештрафа нуждается в улучшении
The criminal-law adjusting of punishment in the type of fine needs perfection
Keywords: покарання; штраф; потерпілий; право; злочинець; наказание; штраф; потерпевший; преступник; penalty; fine; victim; law; crime